University proceedings. Volga region. Medical sciences - A.S. Reutov; E.A. Koretskaya; E.V. Goryacheva; O.O. Ilyunina (Известия высших учебных заведений. Поволжский регион: Медицинские науки)
Modern research defines stress as one of the factors in the development of periodontitis. However, the pathophysiology of stress has an extremely ramified mechanism affecting several body systems at once. Of course, stress can be regarded as one of the linksin the pathogenesis of periodontitis, but only in combination with many other factors such as oral microflora, lifestyle, nutrition, heredity, etc. As a result, the periodontium acts as one of the body structures that can be exposed to the pathological effects of stress. 53 domestic and foreign sources containing information on the physiology and impact of stress on the human body and periodontal tissues were analyzed. A systematic search of articles was performed in the PubMed and eLibrary databases. Stress is an important factor influencing the occurrence and progression of changes in periodontal tissues. An individual approach to optimizing the level of psychoemotional stress can be regarded as one of the methods for preventing diseases such as periodontitis.